2018
DOI: 10.3390/ijms19092833
|View full text |Cite
|
Sign up to set email alerts
|

Altered Glucosinolate Profiles and Expression of Glucosinolate Biosynthesis Genes in Ringspot-Resistant and Susceptible Cabbage Lines

Abstract: Ringspot, caused by the fungus Mycosphaerella brassicicola, is a serious disease of Brassica crops worldwide. Despite noteworthy progress to reveal the role of glucosinolates in pathogen defense, the host–pathogen interaction between cabbage (Brassica oleracea) and M. brassicicola has not been fully explored. Here, we investigated the glucosinolate profiles and expression of glucosinolate biosynthesis genes in the ringspot-resistant (R) and susceptible (S) lines of cabbage after infection with M. brassicicola.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 57 publications
3
18
0
Order By: Relevance
“…Total GSL level was increased in leaves of B. rapa resistance cultivar upon infection of Leptosphaeria maculans and Fusarium oxysporum; whereas GSL was decreased in the susceptible line [43]. Recently, an increased level of GSL content was reported in resistance cabbage lines against ring spot disease [34]. A similar result was also found in the susceptible B. napus cultivars infected with Alternaria brassicae pathogen [43,44].…”
Section: Gsl Compounds Varied In the Leaf Tissues Of Resistant And Susupporting
confidence: 61%
See 2 more Smart Citations
“…Total GSL level was increased in leaves of B. rapa resistance cultivar upon infection of Leptosphaeria maculans and Fusarium oxysporum; whereas GSL was decreased in the susceptible line [43]. Recently, an increased level of GSL content was reported in resistance cabbage lines against ring spot disease [34]. A similar result was also found in the susceptible B. napus cultivars infected with Alternaria brassicae pathogen [43,44].…”
Section: Gsl Compounds Varied In the Leaf Tissues Of Resistant And Susupporting
confidence: 61%
“…The GSL composition of the cabbage leaf samples was estimated as desulfo-GSL from three biological replicates for each of the control, mock-treated and Xcc infected plants using a modified Plants 2020, 9, 1121 4 of 16 HPLC method as previously described [33,34]. Frozen leaf tissue was treated with methanol and stored at −80 • C and then ground to a very fine powder.…”
Section: Glucosinolates Identification Quantification and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…This results supported the fact that glucosinolate mediated resistance in cabbage plants differs between seedling and adult stages. In recent studies, resistant cabbage plants inoculated with S. sclerotiorum and M. brassicicola showed increased accumulation of GIV (Abuyusuf et al, 2018a;Abuyusuf et al, 2018b) indicating its importance in resistance against diverse fungal infection.…”
Section: Accumulation Of Giv and Other Aliphatic Glucosinolates Diffementioning
confidence: 99%
“…By contrast, Li et al (1999a) in B. napus, reported a positive correlation between indolic glucosinolates induced upon the infection of Sclerotinia sclerotiorum and resistance of plants. In cabbage, inoculation of both resistant and susceptible plants with S. sclerotiorum and Mycosphaerella brassicicola revealed that both aliphatic and indolic glucosinolates raise in contents in the resistant lines (Abuyusuf et al, 2018a;Abuyusuf et al, 2018b). Furthermore, a recent study described possible mechanisms of overcoming glucosinolate-myrosinase-isothiocyanate defense system of Phoma lingam and Verticillium dahliae as these fungi species may degrade some primary glucosinolates to a less toxic level (Rahimi and Siamak, 2020).…”
Section: Introductionmentioning
confidence: 99%